Exploring methane emissions in Africa - Faye, Jean Paul Latyr; Dia, Mansour; Dia, Khadim; Ly, Racine (AKADEMIYA2063, 2024)
In the 21st century, climate change has emerged as one of the most pressing human and environmental crises. The primary driver of this global challenge is the accumulation of greenhouse gases (GHGs), such as carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O), in the atmosphere. In analyzing Africa’s contribution to the global GHG budget,1 it is essential to consider two factors: the absolute emissions of the continent and their role in the global carbon cycle. It is well known that Africa’s GHG emissions are relatively low on a per capita basis, but they are rising due to population growth, urbanization, and increased human activities. According to new studies (Mostefaoui et al. 2024), Africa’s methane emissions are steadily increasing. This trend reflects both agricultural development and environmental factors, such as increased forest fires due to aridity and climate variability, including the effects of El Niño.